Glyoxalase-1 overexpression in bone marrow cells reverses defective neovascularization in STZ-induced diabetic mice. (20th November 2013) - Vulesevic, Branka; McNeill, Brian; Geoffrion, Michele; Kuraitis, Drew; McBane, Joanne E.; Lochhead, Marina; Vanderhyden, Barbara C.; Korbutt, Gregory S.; Milne, Ross W.; Suuronen, Erik J.
Abstract: Aims: Methylglyoxal (MG) accumulates in diabetes and impairs neovascularization. This study assessed whether overexpressing the MG-metabolizing enzyme glyoxalase-1 (GLO1) in only bone marrow cells (BMCs) could restore neovascularization in ischaemic tissue of streptozotocin-induced diabetic mice. Methods and results: After 24 h of hyperglycaemic and hypoxic culture, BMCs from GLO1 overexpressing and wild-type (WT) diabetic mice were compared for migratory potential, viability, and mRNA expression of anti-apoptotic genes (Bcl-2 and Bcl-XL). In vivo, BMCs from enhanced green fluorescent protein (eGFP) mice that overexpress GLO1 were used to reconstitute the BM of diabetic mice (GLO1-diabetics). Diabetic and non-diabetic recipients of WT GFP + BM served as controls (WT-diabetics and non-diabetics, respectively). Following hindlimb ischaemia, the mobilization of BMCs was measured by flow cytometry. In hindlimbs, the presence of BM-derived angiogenic (GFP + CXCR4 + ) and endothelial (GFP + vWF + ) cells and also arteriole density were determined by immunohistochemistry. Hindlimb perfusion was measured using laser Doppler. GLO1-BMCs had superior migratory potential, increased viability, and greater Bcl-2 and Bcl-XL expression, compared with WT BMCs. In vivo, the mobilization of pro-angiogenic BMCs (CXCR4 +, c-kit +, and Flk + ) was enhanced post-ischaemia in GLO1-diabetics compared to WT-diabetics. A greater number of GFP + CXCR4 + and GFP + vWF + BMCs incorporated into the hindlimb tissue of GLO1-diabetics and non-diabetics than in WT-diabetics. Arteriole and capillary density and perfusion were also greater in GLO1-diabetics and non-diabetics. Conclusion: This study demonstrates that protection from MG uniquely in BM is sufficient to restore BMC function and neovascularization of ischaemic tissue in diabetes and identifies GLO1 as a potential therapeutic target.